Development of sensory organs in larvae of mouse grouper, Cromileptes altivelis - Mukai, Yukinori; Daning Tuzan, Audrey; Muhamad Shaleh, Sitti Raehanah; Senoo, Shigeharu (INOC-UMS, 2006)
This study was conducted to clarify the development of the sensory organs with larval growth in mouse grouper Cromileptes altivelis for the purpose of understanding larval behavior and improving larval rearing methods. The newly hatched larvae floated motionless in the rearing tanks. The eyes were only recognized as an outline with undifferentiated retina. The inner ears were only oval-shaped vesicles. The 1-day-old larvae still showed suspended posture, and were repeatedly moving up and down in the water. The eyes of 1-day-old larvae had a lens and several layered retina, and the olfactory pits were opened with epithelium cilia. Two-day-old larvae swam with a horizontal posture, the eyes were slightly pigmented, the mouth was open, and lower jaw movements were observed. Three-day-old larvae commenced ingesting rotifer Brachionus sp. Ten-day-old larvae showed strong phototaxis. At 20 days old, taste buds were observed in the buccal cavity..